MANAGEMENT TO THE EXCELLENCE OF PRIVATE SCHOOLS IN NONTHABURI - Kettanom, Thasporn (Academic Journal Phranakhon Rajabhat University, 2021)
The purposes of the study were to: 1) determine the components of private school management to excellence in Nonthaburi; 2) evaluate the suitability and feasibility of the private school management to excellent model. The research process consisted of three steps: 1) analyzing documents concerning school management to excellence model, 2) analyzing data of 21 experts in school management using Delphi technique, and 3) evaluating 159 school administrators’ opinions on the suitability and feasibility of the management to excellence in the academic year 2020. The research instruments for data collection were an interview form and a rating scale questionnaire with the reliability index of 0.98. The data was analyzed by percentage, mean, standard deviation, and median and inter quartile ranges were also computed to test the consensus of the study. Based upon the findings, it was concluded that 1. All of the 21 experts strongly agreed that the management to excellence of private schools in Nonthaburi model consisted of four factors including personnel management, general management, academic management and budget management 2. From the evaluation of opinions of 159 school administrators, it was found that the majority agreed with the guidelines for management to excellence of private schools in Nonthaburi at a high level.